Corporate and product brands: do they improve SMEs' performance?. Issue 1 (2014) - ,; ,; ,
Abstract : Purpose – The aim of this paper is to investigate the impact of brands on small to medium‐sized enterprise (SME) performance in the fashion industry, trying also to shed light on the different effect that corporate and product brands may produce. Design/methodology/approach – The approach uses cross‐sectional time series regression to investigate the relationship between trademarks and sales, controlling for firm size. A purposive sampling technique is adopted, focusing on a sample of Italian SMEs in the fashion industry. Findings – Results indicate that trademarks do have a positive impact on SMEs' performance in the fashion industry, and in particular corporate trademarks seem to be effective in producing a sales increase, while product trademarks do not. Research limitations/implications – The main limit of this research is that no variable mediating the relationship between trademarks and performance was considered. Furthermore, the number of trademarks may not capture all the dimensions of brand. Practical implications – The most important aspect is that SME managers in the fashion industry could benefit from a trademarking strategy; in particular, investments in building a strong corporate brand, thus concentrating SMEs' effort, instead of having many different product brands, seems to create greater effect in the minds of consumers, and thus result in sales increases. Originality/value – This paper is one of first attempts to shed light on the issue regarding the association between SMEs' branding strategy and performance. Moreover, the distinction between corporate and product brands represents an innovative element in this type of study. Acknowledgements : This research has been supported by the Fondazione Studi Universitari di Vicenza (FSU) which grants scholarships to young researchers at the Department of Management and Engineering of the University of Padua. A special thanks to Professor Adriano Paggiaro for his support during the statistical analysis.